Strategi Komunikasi Dinas Kesehatan dalam Sosialisasi Penurunan Stunting Melalui Kegiatan Posyandu di Desa Cihuni - Ramdani, Ramdani; Adnan, Iis Zilfah (Dinasti Research, 2025)
This study examines the communication strategy of the Health Office and the cadres of the Cihuni Village Posyandu, Pangatikan District, Garut Regency in an effort to accelerate stunting reduction. Using a qualitative approach, data was collected through in-depth interviews, observations, and documentation of posyandu cadres, village officials, and health center workers. The results of the study show that the success of stunting prevention socialization is influenced by three main factors: the preparation of simple and relevant nutrition messages, the selection of appropriate communication channels, and the credibility of communicators. A combination of face-to-face through posyandu, home visits, and the use of digital media such as WhatsApp has been shown to increase the participation of mothers under five and encourage behavior change, such as increased adherence to exclusive breastfeeding and monitoring of child growth. The obstacles faced include low attendance of residents during the harvest season, limited educational media, and diverse health literacy. However, the community's response showed an increase in knowledge and active involvement in posyandu activities, indicating the effectiveness of the communication strategy implemented. This research emphasizes the importance of synergy between village governments, health workers, and posyandu cadres in conveying contextual and sustainable health messages to achieve the national target of stunting reduction.